No escape [videorecording (DVD)] - Dowdle, John Erick; Bell, Lake, 1979-; Wilson, Owen, 1968-; Brosnan, Pierce (Anchor Bay Entertainment, 2015)
How far will one man go to protect the ones he cares about most in the world? An intense international thriller, centers on an American businessman as he and his family settle into their new home in Southeast Asia. Suddenly finding themselves in the middle of a violent political uprising, they must frantically look for a safe escape as rebels mercilessly attack the city.